Parachromis managunesis (Günther, 1867): Keberadaan Ikan Predator Asing di Pulau Lombok, Nusa Tenggara Barat: Jaguar chiclid di Lombok - Veryl Hasan; Maheno Sri Widodo (Samakia : Jurnal Ilmu Perikanan, 2021)
The entry of foreign predatory fish into Indonesian open waters had the potential as a disease vector, predation, and damaging food webs that would have a systemic impact on the local ecosystem. In this study, we report the presence of the foreign predatory fish Jaguar cichlid Parachromis managuensis (Günther, 1867) from Central America in the Lingsar River, West Lombok Regency. This record is the first time for this species in Lombok, where previously this fish was found in Java. A description of the morphological characters of the captured specimens is provided in the discussion.